The Influence of Debt Maturity and Environmental Social Governance on Investment Efficiency - M. Trihudiyatmanto (UP2MF Fakultas Ekonomi dan Bisnis, Universitas Sains Al-Qur'an (UNSIQ) Jawa Tengah di Wonosobo, 2025)
Purpose – This study aims to demonstrate the influence of Debt Maturity and Environmental Social Governance (ESG) on Investment Efficiency in mining companies listed on the Indonesia Stock Exchange (IDX) for the 2022-2025 period. Methodology – This study employed a quantitative method with an associative approach. The population in this study was mining companies listed on the IDX. Through purposive sampling, a sample of 23 companies was obtained, with a total of 92 observations. The data analysis method used multiple linear regression analysis, processed using SPSS version 25 software. Findings – The results of the study indicate that: (1) Debt Maturity has a negative and significant effect on Investment Efficiency, with a calculated t-value of -7.781 and a significance level of 0.000 <0.05. (2) Environmental Social Governance (ESG) has an effect on Investment Efficiency, with a calculated t-value of 2.183 and a significance level of 0.032 >0.05. Simultaneously (F-test), all variables had a significant effect, with an F-value of 17.790. Limitations – This study is limited by the sample size, which focused only on the mining sector, and by the fact that several companies did not publish complete ESG reports during the study period. Future research agenda – Future researchers are advised to expand the research object to other sectors or add other independent variables, such as audit quality or audit committees, which may have a stronger influence on investment efficiency.